Assessing ecosystem platforms impact on investment attractiveness of companies - A. A. Aliev; B. A. Tursunov; D. S. Konygin (Вестник университета)
Historically low interest rates and active stimulation of national economies through the large-scale use of quantitative easing techniques by central banks have led to a rapid increase in financial assets value on world markets. The Russian economy is experiencing rapid growth in real estate values, prices for durable goods, and general inflation. All these factors have led to a large-scale increase in brokerage accounts and active growth of private investors on the Moscow Interbank Currency Exchange. As the number of the latter grows, their savings, which are redirected into investments in the financial market, have an increasing weight in shaping trends in the Russian market. At the same time, there is a need to understand the existing risks and methods of dealing with them. Consequently, there is a growing need for a systematic and strategic approach, methods, and criteria for assessing the investment attractiveness of companies. In addition, the struggle among public companies on the Russian stock market is intensifying, and the issue of improving investment attractiveness and business efficiency and developing tools to implement these processes is becoming more and more urgent.